Martabat Manusia dalam Dunia Kerja : Tela’ah Ensiklik Laborem Exercens (Jurnal Pendidikan Agama dan Teologi, 2024)
The modern world of work often prioritizes productivity and ignores the human dimension of workers. This article examines the concept of human dignity in the world of work based on Pope John Paul II's encyclical Laborem Exercens. The encyclical asserts that work is not merely a means to fulfill economic needs, but also an expression of human dignity and participation in the work of creation. Work has a subjective value that transcends material value, so human beings should always be the center of attention in work activities. In addition, Laborem Exercens highlights the importance of justice in employment relations, respect for workers' rights, solidarity and balance between material and spiritual aspects. This article aims to explore the application of these principles in today's world of work in order to create a more humane, just and sustainable work environment. By basing on the values contained in the encyclical Laborem Exercens, the world of work can become a means of building an inclusive and dignified community, where human well-being takes precedence over mere economic efficiency. This analysis is relevant as a reflection for modern society in realizing a world of work that respects the dignity of every individual.